Når borger og kommune mødes digitalt - Flebbe, Anja (Klart språk i Norden, 2014)
Citizens expect digital communication with public authorities to be as smooth as other online services. However, it is not easier to claim benefits and services only because it is done digitally. For municipalities and other public authorities, it is expensive when the citizens makes phone calls or show up at city hall, rather than using the online channels – and the municipalities experience budget reductions because of the savings digitization is meant to generate. The Municipality of Horsens have experienced success by, inspired by e-commerce, seeing digital self service as a product to be sold. The approach changes the rhetoric and language in the digital communication between citizen and public authority, and emphasizes the need for a holistic approach to digital self service. Different target groups present different challenges: the older generation may have difficulties in the digital interactions, whereas the younger age groups may have a hard time understanding certain key concepts in the language used by the municipality and other authorities.